Method for increasing SCX value of titanium dioxide

Through the surface coating activity treatment method, organic coating is used with silane coupling agent and trimethylolpropane, the problem of improving the SCX value of titanium dioxide is solved, and the performance of titanium dioxide pigment is significantly improved, and the advantages of environmental protection and wide application range are provided.

CN119529561APending Publication Date: 2025-02-28SHANDONG DAWN TITANIUM IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411720114.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively increase the SCX value of titanium dioxide, and the traditional methods have limitations in scope of application and environmental protection problems.

Method used

A surface coating active treatment method is adopted, through grinding, beating dispersion, inorganic coating and organic coating, silane coupling agent and trimethylolpropane are used as organic coating agents to control pH and temperature to ensure uniform coverage of the titanium dioxide surface.

Benefits of technology

The SCX value of titanium dioxide is significantly improved, its pigment performance and optical performance are improved, and the method is simple to operate, environmentally friendly and has a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The method for increasing the SCX value of the titanium dioxide adopts a surface coating active treatment method and comprises the following steps: S1, grinding, S2, pulping and dispersing, S3, inorganic coating, S4, organic coating and S5, curing and maintaining. According to the preparation method, efficient dispersion of titanium dioxide is promoted by mixing the dispersing agent, agglomeration of titanium dioxide particles and coating agent particles can be avoided by adopting a form of first inorganic coating and then organic coating, so that the titanium dioxide particles and the coating agent are uniformly dispersed, and the titanium dioxide of which the particle size D50 is equal to 0.4-0.5 mu m is obtained. According to the invention, special organic coating agent raw materials and a specific proportion are adopted, so that the SCX value of the coated titanium dioxide is further effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium dioxide, and in particular to a method for improving the SCX value of titanium dioxide. Background Art

[0002] In the series of pigment performance index systems of titanium dioxide, there are mainly parameters such as L, a, b, TCS and SCX. Among them, SCX is the key indicator of the pink phase of titanium dioxide, and its value range is usually between 2-6. When the SCX index decreases, the hue of titanium dioxide tends to be yellow. Conversely, as the index increases, the pink phase of titanium dioxide turns to blue. At this time, titanium dioxide appears to be whiter visually. With the continuous advancement of production technology, the current market requirements for blue phase indicators are gradually rising. Specifically, customers expect the visual effect of titanium dioxide to be whiter, which requires the improvement of the SCX index. In this process, changing the coating activity on the surface of titanium dioxide has become a key control node.

[0003] The surface coating activity of titanium dioxide directly affects many of its performances: on the one hand, good coating activity can optimize the optical properties of titanium dioxide, so that it can show stable and excellent color effects under different lighting conditions; on the other hand, it also plays a vital role in the chemical stability of titanium dioxide, which can enhance its corrosion resistance and anti-aging ability, and extend its service life in various application environments. In addition, suitable coating activity can also improve the dispersibility of titanium dioxide, making it easier to disperse evenly in different media, thereby improving the overall quality and performance of the product. Therefore, in-depth research and precise control of the surface coating activity of titanium dioxide is of great practical significance for meeting the market demand for high-quality titanium dioxide.

[0004] CN118126541B discloses a method for improving the SCX value of a titanium dioxide colored base phase, by using dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and 3-aminopropyltriethoxysilane in an organic treatment agent, which allow the titanium dioxide surface to have both a charge repulsion effect and a steric hindrance effect, thereby improving the dispersibility of the titanium dioxide in a dispersion medium, thereby improving its SCX value, and solving the problem that the current titanium dioxide treatment method for improving the SCX value is not universal and has a long process flow. However, the method still has the problem of limited scope of application, and there are also environmental issues due to the addition of organic solvents.

[0005] Zhao conducted a single-factor variable experiment to study the effects of changes in the content of sodium and potassium ions on the SCX of the rutile titanium dioxide coloring base phase. He concluded that, when the content of other elements remains unchanged, increasing the sodium content can reduce the SCX of the rutile titanium dioxide coloring base phase, and that potassium, which is in the same main group as sodium, also has the effect of reducing the SCX of the rutile titanium dioxide coloring base phase. In the production process of rutile titanium dioxide, sodium is generally not used for salt treatment adjustment. Sodium is mainly affected by the production water quality. In order to obtain a product coloring base phase that meets product requirements, the water source and water quality should be controlled. Potassium salt is used as a structure and color adjustment and control agent. The amount of potassium added in the salt treatment formula should be reasonably adjusted during production. However, although the article concluded that the SCX of the titanium dioxide coloring base phase can be improved after the potassium salt content is reduced, the performance index of titanium dioxide pigment is not a single index. There are also factors such as product whiteness, brightness and application performance. These factors have not been fully and comprehensively considered in this study. Therefore, there is a problem that the overall index of titanium dioxide needs to be further improved (China Coatings, 2019,34:11;59-64).

[0006] In summary, developing a simple, economical, environmentally friendly and versatile method for enhancing titanium dioxide SCX to improve the comprehensive performance of titanium dioxide pigments has become a technical problem that needs to be overcome urgently in this field. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a surface coating activity treatment method for enhancing titanium dioxide SCX. The method is simple to operate, and the organic coating agents used are silane coupling agent and trimethylolpropane. Under normal use and treatment, it will not cause pollution to the environment. The method has a wide range of applications, and the overall indicators of titanium dioxide obtained by the treatment method have achieved an overall breakthrough compared with those obtained by traditional methods. The specific implementation plan is as follows:

[0008] A method for significantly improving the surface coating activity of titanium dioxide SCX, comprising the following steps:

[0009] Step 1: Grinding

[0010] Grinding the crude titanium dioxide product into particle sizes to obtain a ground crude titanium dioxide product;

[0011] Step 2: Beating and Dispersion

[0012] Add the ground titanium dioxide crude product described in step 1 into water, stir for 2 minutes, then add the mixed dispersant, stir at a rate of 250-500 r / min, adjust the pH value, heat and continue stirring for 30-90 minutes to obtain a titanium dioxide homogeneous liquid;

[0013] Step 3: Inorganic coating

[0014] Use an inorganic coating agent to inorganically coat the titanium dioxide homogeneous liquid described in step 2, set the temperature to 45-60° C., and the total addition time of the inorganic coating agent is 3-5 hours to obtain an inorganic coated titanium dioxide homogeneous liquid;

[0015] Step 4: Organic coating

[0016] The inorganically coated titanium dioxide homogeneous liquid described in step 3 is organically coated by adding an organic coating agent by a wet method, wherein the organic coating agent is a mixture of a silane coupling agent and trimethylolpropane, wherein the mass ratio of the silane coupling agent to the trimethylolpropane is (1-9):(9-1), to obtain an organically coated titanium dioxide homogeneous liquid;

[0017] Step 5: Aging and maintenance

[0018] The organically coated titanium dioxide homogeneous liquid described in step 4 is matured for 2-5 hours, with a stirring rate of 400-450 r / min, a temperature of 45-60° C., and a pH of 7.5-8.6 to obtain titanium dioxide after surface coating active treatment.

[0019] Furthermore, in step 1, the grinding medium is any one of 0.5-0.8 mm zirconium beads, glass beads, ceramic beads, and steel beads, with a filling ratio of 50-60%.

[0020] Furthermore, in step 1, the specific steps of grinding are: the titanium dioxide is sequentially passed through a roller mill with a linear speed of 2-5 m / s for 120-180 min, a colloid mill with a rotation speed of 20-50 r / min for 240-360 min, and a sand mill with a dispersion disk speed of 2800-3000 rpm for 420-520 min.

[0021] Furthermore, in step 1, titanium dioxide particles with a particle size of D50=0.408-0.485 μm are obtained after grinding.

[0022] Furthermore, in step 2, the mixed dispersant is a mixture of sodium silicate and sodium hexametaphosphate, wherein the mass ratio of sodium silicate to sodium hexametaphosphate is 1:4-6, and the amount of the dispersant added is 0.3-0.9% of the mass of the titanium dioxide, based on the mass of the titanium dioxide.

[0023] Further, in step 2, a concentration of 100-200 g / L of Al 2 (SO 4 ) 3 The solution is adjusted to have a pH value of 10-10.5 and a temperature of 45-60°C.

[0024] Further, in step 3, the inorganic coating agent is H 2 SO 4 and NaSiO 3 、Al 2 (SO 4 ) 3 、NaAlO 2 , NaOH, KSiO 3 , KAlO 2 , any one of KOH.

[0025] Further, in step 3, the step of adding the inorganic coating agent is: adding NaSiO 3 The solution is added dropwise into the titanium dioxide homogeneous liquid, and the pH of the titanium dioxide homogeneous liquid is adjusted to between 10.3-10.6. The dripping is completed within 1 hour, and then Al2O3 with a concentration of 100-200 g / L is added at the same time. 2 (SO 4 ) 3 solution and 20wt% NaOH solution, Al 2 (SO 4 ) 3 The dripping speed ratio of NaOH is 1:1, the dripping speed is 23-29 drops / min, and the surface inorganic coating is carried out by stirring at a stirring rate of 250-500r / min. After the dripping is completed, stirring is continued for 0.5-2h, and then 10wt% H 2 SO 4 , the dripping rate is 13-17 drops / min, and the pH is controlled at 7.5-8.

[0026] Further, in step 4, trimethylolpropane is added to 100 mL of water, and heated with stirring using a magnetic rotor, maintaining the temperature at 35-45° C., the rotation speed at 300-400 rpm, and the stirring time at 15-20 min. Then, a silane coupling agent is added dropwise and stirred into a uniform suspension for 30 min to obtain the organic coating agent.

[0027] Furthermore, in step 4, the organic coating step is: adding the organic coating agent dropwise into the inorganic coated titanium dioxide homogeneous liquid described in step 3 within 2-3 hours, the temperature is 50-60°C, the dripping rate is 10-20 drops / min, stirring for organic coating, the stirring rate is 250-500r / min, and the organic coated titanium dioxide homogeneous liquid is obtained.

[0028] Furthermore, in step 4, the silane coupling agent is any one of vinyl triethoxy silane (A151), vinyl trimethoxy silane (A171), and vinyl tri (β-methoxyethoxy) silane (A172).

[0029] Furthermore, in step 4, when the mass ratio of the silane coupling agent to trimethylolpropane is 3:2, the SCX value of the titanium dioxide reaches a maximum value.

[0030] Furthermore, in step 5, the particle size of the titanium dioxide after the surface coating activation treatment is D50=0.4-0.5 μm.

[0031] The beneficial effects of the present invention are as follows:

[0032] 1. The use of mixed dispersants can effectively promote the efficient dispersion of titanium dioxide. This dispersion effect allows the titanium dioxide particles to be evenly distributed in the system, avoiding the aggregation of particles and providing a good foundation for the subsequent coating process. At the same time, the form of inorganic coating followed by organic coating can effectively avoid the agglomeration of titanium dioxide particles and coating agent particles, so that the titanium dioxide particles and the coating agent can be evenly dispersed, ensuring that the coating agent can fully cover the surface of the titanium dioxide particles, thereby promoting the uniformity of the dispersion of the coating agent. Through the synergistic effect of a series of measures, the SCX value of titanium dioxide after coating can be effectively improved, so that its color performance and optical properties can be significantly improved.

[0033] 2. Compared with the prior art, the uniqueness of the present invention also lies in the fact that in the surface treatment process, the pH adjustment is cleverly used to change the formation morphology of the aluminum film. By precisely controlling the pH value, the aluminum film can form a more uniform and dense structure on the surface of titanium dioxide, thereby improving the surface properties of titanium dioxide; in addition, the generation and coating speed of the aluminum film are controlled by temperature adjustment. Appropriate temperature conditions can ensure that the generation process of the aluminum film is stable and the coating speed is moderate, which not only ensures the integrity of the coating, but also improves the efficiency of the coating; this precise control of pH and temperature can effectively complete the performance change of the titanium dioxide surface, thereby significantly improving the SCX value of titanium dioxide.

[0034] 3. The method of the present invention not only improves the SCX value of titanium dioxide, but also has the advantages of simple operation and strong controllability. By selecting the dispersant and optimizing the coating process, the performance of titanium dioxide can be precisely controlled, which not only helps to improve the quality stability of the product, but also can meet the personalized needs of titanium dioxide in different application scenarios; in addition, the method also has good versatility and can be applied to various types of titanium dioxide, providing an effective technical means for the development of the titanium dioxide industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The pigment index changes of Example 1 of the present invention;

[0036] Figure 2 The pigment index changes of Example 2 of the present invention;

[0037] Figure 3 The pigment index changes of Example 3 of the present invention;

[0038] Figure 4 The pigment index changes of Example 4 of the present invention;

[0039] Figure 5 The pigment index changes of comparative example 1 of the present invention;

[0040] Figure 6 The pigment index changes of comparative example 2 of the present invention;

[0041] Figure 7 The pigment index changes of comparative example 3 of the present invention;

[0042] Figure 8 The pigment index changes of Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be described in detail below in conjunction with specific embodiments of the present invention. The described embodiments are only a part of the present invention, and the present invention is not limited to the embodiments described below.

[0044] In order to avoid abnormal experimental results caused by the abnormality of a single crude product and to increase the credibility of the experiment, the present invention uses 4 batches of crude titanium dioxide to carry out an experiment to improve the SCX value of titanium dioxide. The specific operation is as follows: 4000g of crude titanium dioxide A, B, C, and D from different batches are taken, and the 4 portions of crude products are divided into two equal portions, respectively recorded as A1, B1, C1, D1 and A2, B2, C2, D2, among which A1, B1, C1, and D1 are treated by the surface coating activation method of the present invention, and A2, B2, C2, and D2 are treated by the traditional single variable method.

[0045] Embodiment 1:

[0046] Step 1: Grinding

[0047] 1000g of the crude titanium dioxide A was successively subjected to roller milling at a linear speed of 2m / s for 120min, colloid milling at a rotation speed of 20r / min for 240min, and sand milling at a dispersion disk rotation speed of 2800rpm for 420min. The grinding medium was 0.8mm zirconium beads with a filling ratio of 60%, to obtain the ground titanium dioxide A. The particle size of the ground titanium dioxide A was measured to be D50=0.457-0.485μm;

[0048] Step 2: Beating and Dispersion

[0049] Take 500g of the ground titanium dioxide A in step 1, record it as titanium dioxide A1, add titanium dioxide A1 into water, and use 100g / L Al 2 (SO 4 ) 3 The crystal was adjusted to pH = 10.5, the temperature was maintained at 60 ° C, and stirred for 2 minutes to obtain a titanium dioxide slurry, 100 g / L of sodium silicate solution and 100 g / L of sodium hexametaphosphate solution were prepared into a mixed solution according to a mass ratio of 1:5, 30 mL of the mixed solution was added to the titanium dioxide slurry, and stirred for 30 minutes at a stirring rate of 350 r / min to obtain a titanium dioxide homogeneous liquid;

[0050] Step 3: Inorganic coating

[0051] Within 1 hour, 200g / L NaSiO 3 The solution was added to the titanium dioxide homogeneous liquid described in step 2, the pH was adjusted to 10.3, the temperature was set to 56°C, and then Al2O3 at a concentration of 100 g / L was added within 1.3 h. 2 (SO 4 ) 3 solution and 20wt% NaOH solution, Al 2 (SO 4 ) 3 The dripping speed ratio of NaOH was 1:1, the dripping speed was 25 drops / min, the stirring speed was 500r / min, and the stirring was continued for 0.5h after the dripping was completed. Then, 10wt% H 2 SO 4 , the dripping rate is 15 drops / min, the pH is adjusted to 7.8, and an inorganically coated titanium dioxide homogeneous liquid is obtained;

[0052] Step 4: Organic coating

[0053] 0.2 g of trimethylolpropane was added to 100 mL of water, and the mixture was stirred and heated using a magnetic rotor, the temperature was maintained at 40° C., the rotation speed was 300 r / min, and the stirring time was 20 min. Then 0.3 g of A151 was added dropwise, and the stirring time was 30 min. The mixture was stirred into a uniform suspension to obtain an organic coating agent. Within 2 h, the organic coating agent was added dropwise into the inorganic coated titanium dioxide homogeneous liquid described in step 3 at a dropping rate of 10 drops / min and a temperature of 50° C. The mixture was stirred for organic coating at a stirring rate of 500 r / min to obtain an organic coated titanium dioxide homogeneous liquid.

[0054] Step 5: Aging and maintenance

[0055] The organically coated titanium dioxide homogeneous liquid described in step 4 was matured for 2 hours at a temperature of 55° C., a stirring rate of 400 r / min, and a pH of 8 to obtain a finished product A1.

[0056] Embodiment 2:

[0057] Step 1: Grinding

[0058] 1000g of the crude titanium dioxide B was successively subjected to roller milling at a linear speed of 2m / s for 120min, colloid milling at a rotation speed of 20r / min for 240min, and sand milling at a dispersion disk rotation speed of 2800rpm for 420min. The grinding medium was 0.5mm zirconium beads with a filling ratio of 50%, to obtain the ground titanium dioxide B. The particle size of the ground titanium dioxide B was measured to be D50=0.408-0.441μm;

[0059] Step 2: Beating and Dispersion

[0060] Take 500g of the ground titanium dioxide B described in step 1, record it as titanium dioxide B1, add titanium dioxide B1 into water, and use 100g / L Al 2 (SO 4 ) 3 The crystal was adjusted to pH = 10.5, the temperature was maintained at 60 ° C, and stirred for 2 minutes to obtain a titanium dioxide slurry. 100 g / L of sodium silicate solution and 100 g / L of sodium hexametaphosphate solution were prepared into a mixed solution according to a mass ratio of 1:4. 30 mL of the mixed solution was added to the titanium dioxide slurry, and stirred for 30 minutes at a stirring rate of 350 r / min to obtain a titanium dioxide homogeneous liquid;

[0061] Step 3: Inorganic coating

[0062] Within 1 hour, 200g / L NaSiO 3 The solution was added to the titanium dioxide homogeneous liquid described in step 2, the pH was adjusted to 10.3, the temperature was set to 56°C, and then Al2O3 at a concentration of 100 g / L was added within 1.3 h. 2 (SO 4 ) 3 solution and 20wt% NaOH solution, Al 2 (SO 4 ) 3 The dripping speed ratio of NaOH was 1:1, the dripping speed was 25 drops / min, the stirring speed was 500r / min, and the stirring was continued for 0.5h after the dripping was completed. Then, 10wt% H 2 SO 4 , the dripping rate is 15 drops / min, the pH is adjusted to 7.8, and an inorganically coated titanium dioxide homogeneous liquid is obtained;

[0063] Step 4: Organic coating

[0064] 0.2 g of trimethylolpropane was added to 100 mL of water, and the mixture was stirred and heated using a magnetic rotor, the temperature was maintained at 40° C., the rotation speed was 300 r / min, and the stirring time was 20 min. Then 0.3 g of A151 was added dropwise, and the stirring time was 30 min. The mixture was stirred into a uniform suspension to obtain an organic coating agent. Within 2 h, the organic coating agent was added dropwise into the inorganic coated titanium dioxide homogeneous liquid described in step 3 at a dropping rate of 10 drops / min and a temperature of 50° C. The mixture was stirred for organic coating at a stirring rate of 500 r / min to obtain an organic coated titanium dioxide homogeneous liquid.

[0065] Step 5: Aging and maintenance

[0066] The organically coated titanium dioxide homogeneous liquid described in step 4 was matured for 2 hours at a temperature of 45° C., a stirring rate of 400 r / min, and a pH of 7.5 to obtain a finished product B1.

[0067] Embodiment 3:

[0068] Step 1: Grinding

[0069] 1000g of the crude titanium dioxide C was subjected to a roller mill at a linear speed of 2m / s for 120min, a colloid mill at a rotation speed of 20r / min for 240min, and a sand mill at a dispersion disk rotation speed of 2800rpm for 420min. The grinding medium was 0.65mm zirconium beads with a filling ratio of 55%, to obtain the ground titanium dioxide C. The particle size of the ground titanium dioxide C was measured to be D50=0.45-0.466μm;

[0070] Step 2: Beating and Dispersion

[0071] Take 500g of the ground titanium dioxide C described in step 1, record it as titanium dioxide C1, add titanium dioxide C1 into water, and use 100g / L Al 2 (SO 4 ) 3 The crystal was adjusted to pH = 10.5, the temperature was maintained at 60 ° C, and stirred for 2 minutes to obtain a titanium dioxide slurry. 100 g / L of sodium silicate solution and 100 g / L of sodium hexametaphosphate solution were prepared into a mixed solution according to a mass ratio of 1:4. 30 mL of the mixed solution was added to the titanium dioxide slurry, and stirred for 30 minutes at a stirring rate of 350 r / min to obtain a titanium dioxide homogeneous liquid;

[0072] Step 3: Inorganic coating

[0073] Within 1 hour, 200g / L NaSiO 3 The solution was added to the titanium dioxide homogeneous liquid described in step 2, the pH was adjusted to 10.3, the temperature was set to 56°C, and then Al2O3 at a concentration of 100 g / L was added within 1.3 h. 2 (SO 4 ) 3 solution and 20wt% NaOH solution, Al 2 (SO 4 ) 3 The dripping speed ratio of NaOH was 1:1, the dripping rate was 25 drops / min, and the stirring rate was 500r / min. After the dripping was completed, the stirring was continued for 0.5h, and then 10wt% H 2 SO 4 , the dripping rate is 15 drops / min, the pH is adjusted to 7.8, and an inorganically coated titanium dioxide homogeneous liquid is obtained;

[0074] Step 4: Organic coating

[0075] 0.2 g of trimethylolpropane was added to 100 mL of water, and the mixture was stirred and heated using a magnetic rotor, the temperature was maintained at 40° C., the rotation speed was 300 r / min, and the stirring time was 20 min. Then 0.3 g of A151 was added dropwise, and the stirring time was 30 min. The mixture was stirred into a uniform suspension to obtain an organic coating agent. Within 2 h, the organic coating agent was added dropwise into the inorganic coated titanium dioxide homogeneous liquid described in step 3 at a dropping rate of 10 drops / min and a temperature of 50° C. The mixture was stirred for organic coating at a stirring rate of 500 r / min to obtain an organic coated titanium dioxide homogeneous liquid.

[0076] Step 5: Aging and maintenance

[0077] The organically coated titanium dioxide homogeneous liquid described in step 4 was matured for 2 hours at a temperature of 60° C., a stirring rate of 400 r / min, and a pH of 7.8 to obtain a finished product C1.

[0078] Embodiment 4:

[0079] Step 1: Grinding

[0080] 1000g of the crude titanium dioxide D was successively subjected to roller milling at a linear speed of 2m / s for 120min, colloid milling at a rotation speed of 20r / min for 240min, and sand milling at a dispersion disk rotation speed of 2800rpm for 420min. The grinding medium was 0.6mm zirconium beads with a filling ratio of 56%, to obtain the ground titanium dioxide D. The particle size of the ground titanium dioxide D was measured to be D50=0.412-0.455μm;

[0081] Step 2: Beating and Dispersion

[0082] Take 500g of the ground titanium dioxide D in step 1, record it as titanium dioxide D1, add titanium dioxide D1 into water, and add 100g / L Al 2 (SO 4 ) 3 The crystal was adjusted to pH = 10.5, the temperature was maintained at 60 ° C, and stirred for 2 minutes to obtain a titanium dioxide slurry. 100 g / L of sodium silicate solution and 100 g / L of sodium hexametaphosphate solution were prepared into a mixed solution according to a mass ratio of 1:4. 30 mL of the mixed solution was added to the titanium dioxide slurry, and stirred for 30 minutes at a stirring rate of 350 r / min to obtain a titanium dioxide homogeneous liquid;

[0083] Step 3: Inorganic coating

[0084] Within 1 hour, 200g / L NaSiO 3 The solution was added to the titanium dioxide homogeneous liquid described in step 2, the pH was adjusted to 10.3, the temperature was set to 56°C, and then Al2O3 at a concentration of 100 g / L was added within 1.3 h. 2 (SO 4 ) 3 solution and 20wt% NaOH solution, Al 2 (SO 4 ) 3 The dripping speed ratio of NaOH was 1:1, the dripping speed was 25 drops / min, the stirring speed was 500r / min, and the stirring was continued for 0.5h after the dripping was completed. Then, 10wt% H 2 SO 4 , the dripping rate is 15 drops / min, the pH is adjusted to 7.8, and an inorganically coated titanium dioxide homogeneous liquid is obtained;

[0085] Step 4: Organic coating

[0086] 0.2 g of trimethylolpropane was added to 100 mL of water, and the mixture was stirred and heated using a magnetic rotor, the temperature was maintained at 40° C., the rotation speed was 300 r / min, and the stirring time was 20 min. Then 0.3 g of A151 was added dropwise, and the stirring time was 30 min. The mixture was stirred into a uniform suspension to obtain an organic coating agent. Within 2 h, the organic coating agent was added dropwise into the inorganic coated titanium dioxide homogeneous liquid described in step 3 at a dropping rate of 10 drops / min and a temperature of 50° C. The mixture was stirred for organic coating at a stirring rate of 500 r / min to obtain an organic coated titanium dioxide homogeneous liquid.

[0087] Step 5: Aging and maintenance

[0088] The organically coated titanium dioxide homogeneous liquid described in step 4 was matured for 2 hours at a temperature of 55° C., a stirring rate of 400 r / min, and a pH of 7.7 to obtain a finished product D1.

[0089] Comparative Examples 1-4:

[0090] The above-mentioned titanium dioxide crude products A2, B2, C2, and D2 were processed by the traditional single variable method, and the specific steps are as follows:

[0091] Slurry dispersion: Take the above-mentioned titanium dioxide crude products A2, B2, C2, and D2 and add them into water. 2 (SO 4 ) 3 The crystal was adjusted to pH = 10.5, the temperature was maintained at 60 ° C, and stirred for 2 minutes to obtain a titanium dioxide slurry, 100 g / L of sodium silicate solution and 100 g / L of sodium hexametaphosphate solution were prepared into a mixed solution according to a mass ratio of 1:5, 30 mL of the mixed solution was added to the titanium dioxide slurry, and stirred for 30 minutes at a stirring rate of 350 r / min to obtain a titanium dioxide homogeneous liquid;

[0092] Inorganic coating: 100 mL of 100 g / L NaSiO 3 The solution was added to the titanium dioxide homogeneous liquid, the temperature was set to 85°C, and after the addition, it was aged for 0.5h with a stirring rate of 350r / min; then 10wt% H 2 SO 4 The solution was aged for 0.5 h, pH was controlled at 9.5, and 95 mL of 100 g / L Al 2 (SO 4 ) 3 The solution was controlled at pH = 2.5. After the dripping was completed, the mixture was stirred and matured for 0.5 h. 120 mL of 100 g / L NaAlO was added within 2 h. 2 The solution was stirred continuously at a rate of 600 r / min using NaOH solution or H 2 SO 4 The solution was adjusted to pH = 7 to obtain finished products A2, B2, C2, and D2.

[0093] Performance Testing:

[0094] The SCX value of titanium dioxide refers to the color tone of titanium dioxide in black slurry after grinding with black slurry. The specific method is as follows: take 3g of titanium dioxide finished products A1, B1, C1, D1 and A2, B2, C2, D2 and 3g of standard black slurry respectively, mix and apply them on a flat grinder, grind twice, 50 turns each time, to obtain the sample to be tested, then take the sample to be tested on the flat grinder, and use a 60μm wet film preparation device to scrape on the glass plate to obtain the sample to be tested; the composition of the standard black slurry is linseed oil (Harbin Paint Factory), castor oil (Tianjin Hengxing Chemical Reagent Manufacturing Co., Ltd.), carbon black (Japan Mitsubishi MA100), and fumed silica (Evonik) in a ratio of 680:170:18.5:30, and the viscosity value is 1000s; use a spectrocolorimeter (Agera, HunterLab) to measure the three stimulus values ​​X, Y, and Z of each sample to be tested; the standard value X of the three stimulus values ​​is obtained after the spectrocolorimeter is calibrated 标 , Y 标 , Z 标 , calculate the TCS value and SCX value of each sample to be tested according to the following formula:

[0095] TCS=TCS 标 -(Y 标 -Y)×100

[0096] SCX=(ZX)-SCX 标

[0097] The finished pigment indicators obtained from Table 1, Examples 1-4 and Comparative Examples 1-4 are as follows:

[0098] sample D50(μm) L a b TCS SCX Finished product A1 0.457~0.485 95.44~95.57 -1.13~-1.15 1.63~1.88 2030~2050 3.68~4.22 Finished product A2 0.457~0.485 95.44~95.57 -1.13~-1.15 1.77~1.88 2030~2050 3.61~3.71 Finished product B1 0.408~0.441 95.33~95.43 -1.13~-1.15 2.34~2.42 2020~2050 3.26~3.90 Finished product B2 0.408~0.441 95.33~95.43 -1.13~-1.14 2.36~2.42 2030~2050 3.28~3.37 Finished product C1 0.45~0.466 95.63~95.68 -1.15~-1.18 1.51~1.64 2010~2030 4.41~5.01 Finished product C2 0.45~0.466 95.63~95.68 -1.15~-1.17 1.51~1.63 1990~2010 4.40~4.44 Finished product D1 0.412-0.455 95.63~95.68 -1.15~-1.18 1.51~1.64 2010~2030 4.41~5.01 Finished product D2 0.412-0.455 95.63~95.78 -1.16~-1.20 1.51~1.68 1990~2050 4.40~4.44

[0099] From the above data, it can be seen that the SCX value of the finished product A1 (Example 1) is increased by 0.51 points compared with the finished product A2 (Comparative Example 1) using the treatment method of the present application;

[0100] Compared with finished product B2 (Comparative Example 2), finished product B1 (Example 2) increased the SCX value of the finished product by 0.53 points using the treatment method of the present application;

[0101] Compared with finished product C2 (Comparative Example 3), finished product C1 (Example 3) increased the SCX value of the finished product by 0.57 points using the treatment method of the present application;

[0102] Compared with finished product D2 (Comparative Example 4), finished product D1 (Example 4) increased the SCX value of the finished product by 0.57 points using the treatment method of the present application;

[0103] In summary, the present application discloses a surface coating activity treatment method that significantly improves the SCX of titanium dioxide. It promotes efficient dispersion of titanium dioxide by mixing a dispersant, and adopts the form of inorganic coating followed by organic coating to effectively avoid agglomeration of titanium dioxide particles and coating agent particles, so that the titanium dioxide particles and the coating agent are evenly dispersed, which promotes uniform dispersion of the coating agent and effectively improves the SCX value of titanium dioxide after coating.

[0104] Comparative Examples 5-13

[0105] Step 1: Grinding

[0106] 500 g of crude titanium dioxide A was successively subjected to roller milling at a linear speed of 2 m / s for 120 min, colloid milling at a rotation speed of 20 r / min for 240 min, and sand milling at a dispersion disk rotation speed of 2800 rpm for 420 min. The grinding medium was 0.8 mm zirconium beads with a filling ratio of 60%, to obtain ground titanium dioxide A. The particle size of the ground titanium dioxide A was measured to be D50 = 0.457-0.485 μm;

[0107] Step 2: Beating and Dispersion

[0108] Add titanium dioxide A to water and use 100g / L Al 2 (SO 4 ) 3 The crystal was adjusted to pH = 10.5, the temperature was maintained at 60 ° C, and stirred for 2 minutes to obtain a titanium dioxide slurry, 100 g / L of sodium silicate solution and 100 g / L of sodium hexametaphosphate solution were prepared into a mixed solution according to a mass ratio of 1:5, 30 mL of the mixed solution was added to the titanium dioxide slurry, and stirred for 30 minutes at a stirring rate of 350 r / min to obtain a titanium dioxide homogeneous liquid;

[0109] Step 3: Inorganic coating

[0110] Within 1 hour, 200g / L NaSiO 3 The solution was added to the titanium dioxide homogeneous liquid described in step 2, the pH was adjusted to 10.3, the temperature was set to 56°C, and then Al2O3 at a concentration of 100 g / L was added within 1.3 h. 2 (SO 4 ) 3 solution and 20wt% NaOH solution, Al 2 (SO 4 ) 3 The dripping speed ratio of NaOH was 1:1, the dripping speed was 25 drops / min, the stirring speed was 500r / min, and the stirring was continued for 0.5h after the dripping was completed. Then, 10wt% H 2 SO 4, the dripping rate is 15 drops / min, the pH is adjusted to 7.8, and an inorganically coated titanium dioxide homogeneous liquid is obtained;

[0111] Step 4: Organic coating

[0112] Mix xg of A151 and yg of trimethylolpropane, where the values ​​of x and y are listed in Table 2, stir evenly, keep the temperature at 50°C, and drop into the inorganic coated titanium dioxide homogeneous liquid in step 3 within 2 hours at a dropping rate of 10 drops / min, stir for organic coating at a stirring rate of 500r / min, and obtain organic coated titanium dioxide homogeneous liquids 5-13 respectively;

[0113] Step 5: Aging and maintenance

[0114] The organically coated titanium dioxide homogeneous liquid described in step 4 was matured for 2 hours at a temperature of 55° C., a stirring rate of 400 r / min, and a pH of 8 to obtain finished products 5-13 respectively.

[0115] Table 2. Mass ratio of organic dispersants in comparative examples 5-13

[0116] sample x(g) y(g) Finished product 5 0.1 0.9 Finished product 6 0.2 0.8 Finished product 7 0.3 0.7 Finished product 8 0.4 0.6 Finished product 9 0.5 0.5 Finished product 10 0.6 0.4 Finished product 11 0.7 0.3 Finished product 12 0.8 0.2 Finished product 13 0.9 0.1

[0117] Table 3. Pigment indexes of finished products of Comparative Examples 5-13.

[0118] sample L a b TCS SCX Finished product 5 95.68 -1.18 1.63 2020 4.42 Finished product 6 95.55 -1.18 1.88 2030 4.56 Finished product 7 95.68 -1.20 1.84 2020 4.65 Finished product 8 95.69 -1.11 1.77 2040 4.63 Finished product 9 95.69 -1.15 1.77 2030 4.65 Finished product 10 95.64 -1.15 1.77 2050 4.75 Finished product 11 95.55 -1.16 1.68 2050 4.68 Finished product 12 95.42 -1.13 1.69 2030 4.65 Finished product 13 95.46 -1.18 1.68 2040 4.53

[0119] From the pigment indexes in Table 3, it can be seen that the SCX value of Group 6 reaches the highest value. Combined with the index comparison of TCS, Group 6 is selected as the usage ratio of the organic coating agent, that is, the specific mass ratio of silane coupling agent and trimethylolpropane is 3:2.

[0120] The above-mentioned specific embodiments are only specific cases of the present invention. The patent protection scope of the present invention includes but is not limited to the product form and style of the above-mentioned specific embodiments. Any surface coating activity treatment method for improving titanium dioxide SCX that complies with the claims of the present invention and any appropriate changes or modifications made thereto by ordinary technicians in the corresponding technical field shall fall within the patent protection scope of the present invention.

Claims

1. A method for improving the SCX value of titanium dioxide, specifically using a surface coating activation treatment method, characterized in that: The method comprises the following steps: Step 1: Grinding Grinding the crude titanium dioxide product into particle sizes to obtain a ground crude titanium dioxide product; Step 2: Beating and Dispersion Add the ground titanium dioxide crude product described in step 1 into water, stir for 2 minutes, then add the mixed dispersant, stir at a rate of 250-500 r / min, adjust the pH value, heat and continue stirring for 30-90 minutes to obtain a titanium dioxide homogeneous liquid; Step 3: Inorganic coating Use an inorganic coating agent to inorganically coat the titanium dioxide homogeneous liquid described in step 2, set the temperature to 45-60° C., and the total addition time of the inorganic coating agent is 3-5 hours to obtain an inorganic coated titanium dioxide homogeneous liquid; Step 4: Organic coating Adding an organic coating agent by wet method to organically coat the inorganically coated titanium dioxide homogeneous liquid in step 3 to obtain an organically coated titanium dioxide homogeneous liquid; Step 5: Aging and maintenance The organically coated titanium dioxide homogeneous liquid described in step 4 is matured for 2-5 hours, with a stirring rate of 400-450 r / min, a temperature of 45-60° C., and a pH of 7.5-8.6 to obtain titanium dioxide after surface coating active treatment.

2. A method for increasing the SCX value of titanium dioxide according to claim 1, characterized in that: In step 1, the grinding medium is any one of 0.5-0.8 mm zirconium beads, glass beads, ceramic beads, and steel beads, with a filling ratio of 50-60%.

3. The method for increasing the SCX value of titanium dioxide according to claim 1, characterized in that: In step 1, the specific steps of grinding are: the titanium dioxide is sequentially passed through a roller mill with a linear speed of 2-5 m / s for 120-180 min, a colloid mill with a rotation speed of 20-50 r / min for 240-360 min, and a sand mill with a dispersion disk rotation speed of 2800-3000 rpm for 420-520 min.

4. The method for increasing the SCX value of titanium dioxide according to claim 1, characterized in that: In step 1, titanium dioxide particles with a particle size of D50=0.408-0.485 μm are obtained after grinding.

5. The method for increasing the SCX value of titanium dioxide according to claim 1, characterized in that: In step 2, the mixed dispersant is a mixture of sodium silicate and sodium hexametaphosphate, wherein the mass ratio of sodium silicate to sodium hexametaphosphate is 1:4-6, and the amount of the dispersant added is 0.3-0.9% of the mass of the titanium dioxide based on the mass of the titanium dioxide.

6. The method for increasing the SCX value of titanium dioxide according to claim 1, characterized in that: In step 2, the pH value is adjusted to 10-10.5 and the temperature is 45-60°C using an Al2(SO4)3 solution having a concentration of 100-200 g / L.

7. The method for increasing the SCX value of titanium dioxide according to claim 1, characterized in that: In step 3, the inorganic coating agent is any one of H2SO4, NaSiO3, Al2(SO4)3, NaAlO2, NaOH, KSiO3, KAlO2, and KOH.

8. A method for increasing the SCX value of titanium dioxide according to any one of claims 1 or 7, characterized in that: In step 3, the inorganic coating agent is added as follows: a NaSiO3 solution with a concentration of 100-200 g / L is added dropwise into the titanium dioxide homogeneous liquid, the pH of the titanium dioxide homogeneous liquid is adjusted to between 10.3-10.6, and the addition is completed within 1 hour. Then, a 100-200 g / L Al2(SO4)3 solution and a 20 wt% NaOH solution are added simultaneously, the dropwise addition speed ratio of Al2(SO4)3 and NaOH is 1:1, the dropwise addition speed is 23-29 drops / min, the surface is inorganically coated with stirring, the stirring speed is 250-500 r / min, and stirring is continued for 0.5-2 hours after the dropwise addition, and then 10 wt% H2SO4 is added dropwise at a dropwise addition speed of 13-17 drops / min, and the pH is controlled to be 7.5-8.

9. The method for increasing the SCX value of titanium dioxide according to claim 1, characterized in that: In step 4, the step of adding the organic coating agent by wet method is: adding trimethylolpropane to 100 mL of water, stirring and heating with a magnetic rotor, maintaining the temperature at 35-45° C., the rotation speed at 300-400 rpm, and the stirring time at 15-20 min, then adding the silane coupling agent dropwise, stirring into a uniform suspension, and stirring for 30 min to obtain the organic coating agent; within 2-3 h, the organic coating agent is added dropwise into the inorganic coated titanium dioxide homogeneous liquid described in step 3, the temperature is 50-60° C., the dripping rate is 10-20 drops / min, stirring for organic coating, and the stirring rate is 250-500 r / min to obtain the organic coated titanium dioxide homogeneous liquid. Wherein, the mass ratio of the silane coupling agent to the trimethylolpropane is (1-9):(9-1). 10 . The method for improving the SCX value of titanium dioxide according to claim 1 , wherein the particle size of the titanium dioxide after the surface coating activation treatment is D50=0.4-0.5 μm.

Citation Information

Patent Citations

  • A method for improving the SCX value of titanium dioxide coloring base phase

    CN118126541B